Trends in starch-based edible films and coatings enriched with tropical fruits extracts: a review - Kupervaser, María Gabriela (2023)
Petroleum-based food packaging materials are non-degradable and considerably affect the environment. In this context, edible films and coatings for food preservation represent a feasible alternative that could potentially reduce conventional non-biodegradable materials. It has been shown the suitability of starch as a non-toxic, widely available, low-cost and adequate film-forming biopolymer. In addition, natural compounds contained in tropical fruits are of great interest due to their proven antioxidant and antimicrobial properties, which are beneficial for the health of consumers and for obtaining more stable and safe foods. This review focuses on the new trends and benefits of incorporating tropical fruit extracts into starch-based edible films and coatings formulations as a source of bioactive compounds. The starch and fruit resources, extraction techniques, filmmaking methods, assays for determining functional properties and the potential uses of edible films and coatings in the food industry were stated and described.